Takhrij Hadith Types of Major Sins in Islam - Indriyani, Diva Nur; Wibisono, M. Yusuf (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about major sins. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the takhrij hadith within the scope of hadith science, while the material object is the hadith about major sins in the history of Bukhari no. 6182. The results of the research and discussion show that the status of hadith is of authentic quality which is not only maqbul but maqbul ma'mul bih as the basis for practicing Islam in avoiding major sins. This study concludes that the major sins in Islam include associating partners with Allah, disobeying one's parents, killing, and perjury. In addition, the act of adultery is a major sin which is strictly prohibited in Islam.